Analysis of Determinants of Propensity to Independence Based on Behavioral Biases, Emotions, Culture, and Materialism Moderated by Religiosity, Financial Literacy and Job Security - Silviana Isyani, Tina; Warokka, Ari; Gurendrawati, Etty (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to analyze the determinants of Propensity to Indebtedness among civil servants (ASN) and employees/entrepreneurs in Indonesia. The main focus of the research includes the influence of financial behavior biases, emotions, culture, and materialism on the tendency to incur debt, as well as how financial literacy, job security, and religiosity moderate these relationships. A quantitative approach was used in this study, employing an ex post facto design supported by a survey questionnaire. Primary data were collected through an online questionnaire distributed via Google Forms, with 400 respondents selected through simple random sampling. The results show that financial behavior biases, such as overconfidence and aversion regret, have a positive and significant effect on Propensity to Indebtedness. Emotions and culture also have significant influences, where emotional impulsivity and consumption-driven cultural values affect the tendency to incur debt. Materialism was found to strongly influence decisions to incur debt to fulfill lifestyle needs. Additionally, the moderating effect of financial literacy strengthens the relationship between financial behavior biases and Propensity to Indebtedness, indicating that better financial understanding helps individuals make wiser decisions. Job security also strengthens this relationship by providing emotional and financial stability. On the other hand, religiosity weakens the influence of emotions and materialism on Propensity to Indebtedness, although practical approaches are still needed to strengthen these effects. This research contributes academically by expanding insights into financial behavior and debt management, and it provides practical implications for the development of effective financial education programs aimed at improving financial literacy among Indonesian society.